Avaliação da aplicação da otorga de direito de uso dos recursos hídricos no Estado do Ceará - Bezerra, Alina de Moraes (2008)
The present paper has as the objective the application of the Right Granted for the usage of Hydro Resources in Ceara State, considering the importance of it among the other instruments of the National Hydro Resources Policy – NHRP. After the accomplishment of the bibliographical research about the theme, it was presented a historical approach of the water issue in a State and National level, relating the changes in scenarios that once presented resistance against the use of such resources, to the actions taken in order to discipline and to manage its usage specially in the Ceara State. Data collected from the HRS - Hydro Resources Secretariat of Ceara, between 1996 and 2006, aiming, through such, evaluate the application of grant within Ceara State, after 10 years of implementation of the NHRP. Yet scarce, the data evaluated enabled the visualization of the following points: i) the grant of right do not occur in an uniform way among the hydrographical regions; II) non-linear numbers of bestowed rights as for the water use; III) the non-observance of the grant of rights for the effluents dilution; IV) it is urgent the adoption of control and discipline methods for the use of underground water within the State, specially in the Urban Areas and in the High Jaguaribe; and, V)the high incidence of the grants of right without reference to the corresponding flow,, specially for the use of the aquiculture sector. We conclude that without an adequate granting process, and, above all of supervision of the issue of the rights granted, the accomplishment of the objectives proposed by the NHRP will not be possible.